Sigismund III`s efforts to obtain foreign aid for the war against the Turks in 1590 - Milewski, Dariusz (Balcanica Posnaniensia. Acta et studia, 2021)
The paper presents Sigismund III`s efforts to obtain foreign aid in the face of the war against the Turks expected in 1590. Polish efforts in Italy and Reich are discussed, but the main focus is on the imperial court and the Duchy of Prussia, from which the king expected the real help. I present the arguments of both sides and the reasons why Poland did not receive any aid from the emperor, but received it from Duchy of Prussia. I also point to the role of particular interests in bilateral relations between Poland and its political partners as well as the latter ones with the Ottoman Empire, which influenced the decisions on granting or refusing aid to Poland against the Turks.